Exploring the Viability of Exogenous Ketones as Weight Loss Supplements (P21-017-19). (13th June 2019) - Poff, Angela; Koutnik, Andrew; Moss, Sara; Mandala, Sahith; D'Agostino, Dominic
Abstract: Objectives: 70.7% of Americans over 20 years of age are overweight or obese. Currently, the main strategy for weight loss is caloric restriction. Ketone bodies have been shown to facilitate voluntary caloric restriction through altering the appetite stimulating hormone ghrelin. However, these non-toxic ketone bodies have not been evaluated as weight loss supplements. C57BL6J mice were used to determine the weight loss efficacy of exogenous ketones by adding synthetic (R/S 1, 3-Butanediol Acetoacetate Diester and 1, 3-Butanediol) and natural (Beta-hydroxybutyrate and Beta-hydroxybutyrate + Medium Chain Triglycerides) ketogenic agents to standard rodent chow ab-libitum. Methods: Six groups (R/S 1, 3-butanediol acetoacetate diester, 1, 3-butanediol, beta-hydroxybutyrate, beta-hydroxybutyrate + medium chain triglycerides, caloric restriction, standard diet ad-libitum) were housed 2–5 animals per cage and monitored to ensure appropriate acclimation prior to intervention. Mice were treated for two weeks with ketogenic agents, adjusting % of agent daily to ensure 20% weight loss was achieved. Results: All ketogenic agents induced weight loss and voluntary caloric restriction. Weight loss for beta-hydroxybutyrate and beta-hydroxybutyrate + medium chain triglycerides was explained by caloric restriction alone. However, R/S 1, 3-butanediol acetoacetate diester induced weight loss at lower dosages which could not be explained by caloric restriction alone. Conclusions: Taken together, all ketogenic agents may assist in weight loss. However, R/S 1, 3-butanediol acetoacetate diester appears to be a more potent non-toxic ketogenic supplement that facilitates weight loss via both voluntary caloric restriction and caloric restriction-independent mechanisms. Future studies should explore caloric-restriction independent weight loss mechanisms of R/S 1, 3-butanediol acetoacetate diester. Funding Sources: Disruptive Nutrition.